2023
DOI: 10.3171/2022.8.spine22291
|View full text |Cite
|
Sign up to set email alerts
|

Restoring bladder function using motor and sensory nerve transfers: a cadaveric feasibility study

Abstract: OBJECTIVE Bladder dysfunction after nerve injury has a variable presentation, and extent of injury determines whether the bladder is spastic or atonic. The authors have proposed a series of 3 nerve transfers for functional innervation of the detrusor muscle and external urethral sphincter, along with sensory innervation to the genital dermatome. These transfers are applicable to only cases with low spinal segment injuries (sacral nerve root function is lost) and largely preserved lumbar function. Transfer of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…We have had success in a number of pre-clinical canine studies in restoring bladder function by transferring a somatic peripheral nerve (donor choices have included obturator, femoral, sciatic, and genitofemoral nerve branches) to vesical nerves of the IHP located adjacent to or on the bladder wall [21][22][23], which are at the distal ends of the anterior division of the inferior hypogastric plexus (IHP). We have previously demonstrated in several human cadaveric studies that somatic nerve transfer to vesical branches of the IHP is technically feasible using ilioinguinal, femoral, and obturator nerve branches [12,13,24]. However, further clarification of the location, size, and relationships of the vesical branches of the IHP and pelvic ganglion is warranted to assist with their identification during surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have had success in a number of pre-clinical canine studies in restoring bladder function by transferring a somatic peripheral nerve (donor choices have included obturator, femoral, sciatic, and genitofemoral nerve branches) to vesical nerves of the IHP located adjacent to or on the bladder wall [21][22][23], which are at the distal ends of the anterior division of the inferior hypogastric plexus (IHP). We have previously demonstrated in several human cadaveric studies that somatic nerve transfer to vesical branches of the IHP is technically feasible using ilioinguinal, femoral, and obturator nerve branches [12,13,24]. However, further clarification of the location, size, and relationships of the vesical branches of the IHP and pelvic ganglion is warranted to assist with their identification during surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Although the diameter of many lower extremity nerves has been defined through many prior studies, the vesical branches of the IHP have not been equally studied in humans. We previously reported that the mean diameter of vesical branches of the IHP was 2.1 mm when measured using a caliper during anatomical dissections [24] in which the nerve branches were still covered with perineurium, fat, and other fascia. However, histological assessment of the nerves after sectioning (which allows for the distinguishment of nerve versus surrounding connective tissues and fat) revealed smaller actual nerve diameters of 0.32 to just over 1 mm (with a mean of 0.53 ± 0.05 mm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation